PENGARUH TIPE KEPRIBADIAN TERHADAP HASIL BELAJAR MATEMATIKA DENGAN INTERVENSI METODE TIME QUIZ - Faza Miftakhul Farid; Yunni Arnidha; Yesi Budiarti (Universitas Ngudi Waluyo, 2021)
Personality type is a trait that every student has. Personality type will affect the learning outcomes of mathematics after intervention with themethod time quiz. This study entitled